2005
DOI: 10.1196/annals.1356.009
|View full text |Cite
|
Sign up to set email alerts
|

Aging as a Mitochondria‐Mediated Atavistic Program: Can Aging Be Switched Off?

Abstract: Programmed death phenomena have been demonstrated on subcellular (mitoptosis), cellular (apoptosis), and supracellular (collective apoptosis) levels. There are numerous examples of suicide mechanisms at the organismal level (phenoptosis). In yeast, it was recently shown that the death of aging cells is programmed. Many of the steps of programmed cell death are shown to be common for yeast and animals, including mammals. In particular, generation of the mitochondrial reactive oxygen species (ROS) is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 104 publications
0
34
0
Order By: Relevance
“…Based on these phenomena, it has been concluded that at least unicellular organisms possess mechanisms for self-elimination. Such phenomena that we have coined "phenoptosis" [1] are also inherent in multicellular organisms, but their molecular mechanisms are still to be elucidated [2,5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these phenomena, it has been concluded that at least unicellular organisms possess mechanisms for self-elimination. Such phenomena that we have coined "phenoptosis" [1] are also inherent in multicellular organisms, but their molecular mechanisms are still to be elucidated [2,5,6].…”
mentioning
confidence: 99%
“…This hypothesis has been supported by the finding that the oxidation level of DNA, proteins, and lipids increases with aging. This situation can be a consequence of an increase in ROS production or a decrease in the antioxidant defense in old age, or simply a result of the prolonged damaging action of ROS accumulated proportionally to the organism's age [1,2,5,6]. In the framework of the theory of programmed aging, Harman's hypothesis has to be supplemented by an assumption that an increase in the ROS-induced damages with time is controlled by the organism, similarly to any other change occurring during ontogenesis.…”
mentioning
confidence: 99%
“…If all yeast were altruistic, the population would go extinct too. Nevertheless, death of most members can prevent extinction of the population in certain conditions [Skulachev, 2002;Skulachev and Longo, 2005]. However, it is selfish (resistant to apoptosis) yeast that actually survived [Fabrizio et al, 2004].…”
Section: Can Aging Be Altruistically Programmed?mentioning
confidence: 98%
“…The strongest argument for ''altruistic'' programmed aging is that unicellular organisms such as yeast undergo aging and programmed cell death [Skulachev, 2002;Longo et al, 2005;Pozniakovsky et al, 2005;Skulachev and Longo, 2005]. For example, in growthlimiting conditions most yeast (''altruistic yeast'') die, while a few apoptosis-resistant (''selfish'') yeast survive and regrow [Fabrizio et al, 2004].…”
Section: Can Aging Be Altruistically Programmed?mentioning
confidence: 98%
“…Antioxidants which are numerous and it is possible to "regulate" quantitative manifestations of an oxidative stress and, as a result, to eliminate pathologies [11].…”
Section: Introductionmentioning
confidence: 99%